Нейро-нечеткое управление сложными объектами - Ложечников, В. Ф.; Михайленко, В. С. (Видавництво Львівської політехніки, 2011)
This report concerns the neuro-fuzzy adapting controller structure. The hybrid network with assistance of identification object block observes the changes in technological process and tries to correct the control algorithm in order to bring the transition process to permissible quality values.
Keywords: сomplicated object; fuzzy-logic controller; hybrid network; adaptation